Individual Search and Social Networks - Sanjeev Goyal; Stephanie Rosenkranz; Utz Weitzel; Vincent Buskens (Fondazione Eni Enrico Mattei (FEEM), 2014)
The explosion in online social networks motivates an enquiry into their structure and their welfare effects. A central feature of these networks is information sharing: online social networks lower the cost of getting information from others. These lower costs affect the attractiveness of individual search vis-a-vis a reliance on social networks. The paper reports the findings of an experiment on these effects. Our experiment shows that online networks can have large effects. Information acquisition is more dispersed and it is accompanied by denser social networks. Aggregate investment in information acquisition falls, but information available to individuals remains stable, due to increased networking. The overall effect is a significant increase in individual utility and aggregate welfare.
Keywords: D83; D85; 330; Social networks